Current problems of technical training of young ski racers in Russia - Novikova N.B.; Belyova A.N.; Ivanova I.G.; Kotelevskaya N.B. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze the kinematics of skating ski moves of young cross-country skiers and determine ways to optimize the technical training of athletes. Methods and structure of the study. At the Russian Youth Cross-Country Championships, video footage of skating movements on the slopes and on the flat was taken. The biomechanical characteristics of the skating movements of boys aged 14-16 years were calculated in the Dartfish Pro program and compared with the indicators of the strongest ski racers in the world. Results and conclusions. The data obtained made it possible to identify the main technical mistakes of young athletes and suggest ways to improve long-term technical training. The reason for the majority of technical errors among young men is an insufficient level of coordination abilities, in particular, balance, the ability to accurately and timely dose efforts, timely change the mode of muscle operation depending on external conditions, as well as low core stability. It is proposed to change approaches to training children, starting from the initial training stage, to place emphasis on creating a broad foundation of motor skills that allow not only to master a biomechanically advantageous structure of movements, but also to develop the ability to timely vary the magnitude, direction and duration of efforts.